Chirality‐Selective Photoluminescence Enhancement of ssDNA‐Wrapped Single‐Walled Carbon Nanotubes Modified with Gold Nanoparticles. Issue 23 (29th April 2016) - Yang, Juan; Zhao, Qinghua; Lyu, Min; Zhang, Zhenyu; Wang, Xiao; Wang, Meng; Gao, Zhou; Li, Yan
Abstract : In this work, a convenient method to enhance the photoluminescence (PL) of single‐walled carbon nanotubes (SWNTs) in aqueous solutions is provided. Dispersing by single‐stranded DNA (ssDNA) and modifying with gold nanoparticles (AuNPs), about tenfold PL enhancement of the SWNTs is observed. More importantly, the selective PL enhancement is achieved for some particular chiralities of interest over all other chiralities, by using certain specific ssDNA sequences that are reported to recognize these particular chiralities. By forming AuNP–DNA–SWNT nanohybrids, ssDNA serves as superior molecular spacers that on one hand protect SWNT from direct contacting with AuNP and causing PL quench, and on the other hand attract the AuNP in close proximity to the SWNT to enhance its PL. This PL enhancement method can be utilized for the PL analysis of SWNTs in aqueous solutions, for biomedical imaging, and may serve as a prescreening method for the recognition and separation of single chirality SWNTs by ssDNA. Abstract : Selective photoluminescence enhancement for (7, 5) tubes over all other chiralities is observed by dispersing single‐walled carbon nanotube mixtures in single‐stranded DNA (ssDNA) (ATT)4 AT solution and modification with gold nanoparticles. This ssDNA sequence (ATT)4 AT is reported to recognize and enable chromatographic purification of the (7, 5) tubes.